The field study of Age value evidence in the Damascene houses intra muros (Damascus University Journal for engineering sciences, 2025)
Damascus houses intra muros have multiple values, including the age value, which is considered one of the most important, due to its association with allother values, and considering it as a factor for weighting those values, in addition to the role it played in previous archaeological recordings, and the role it could play in determining subsequent preservation priorities.The research dealt with the age value and its role in the Syrian Antiquities Law, and the repercussions of its application. Evidence for the existence of this value was also studied, starting with previous studies, then searching in official documents, ending with the field study, which made it possible to identify evidence for reading and measuring this value. Up to the results of adopting these evidences, through which we present new, unpublished and unknown information that contributes to enhancing the age value of the Damascene houses intra muros, and weighs on other values ​​that it enjoys.
Keywords: Age value evidence; Damascene houses dating; Damascene houses before Ottoman period.